A Group-Based 8-Week Functional Interval-Type Outdoor Training Program Improves Physical Performance in Recreationally Active Adults - Hendker, Anna; Eils, Eric (Frontiers in Sports and Active Living, 2021)
Even though physical activity is an important aspect of health, lack of time or motivation impede people from working out regularly. One type of training program that is both efficient and motivating is high-intensity outdoor fitness. Yet, how this form of training affects recreationally active participants is not well known. To evaluate this, our study had 81 subjects complete a battery of physical performance tests (incremental step test, core stability test and functional fitness test) before and after an 8-week outdoor training intervention. Training procedures included multimodal and high-intensity exercises performed in fixed, small groups. Results showed that the training program produced significant increases in functional and strength exercises (p<.001) for almost all parameters in comparison to a non-intervention control population. Interestingly, trunk stability increased significantly (p<.001) even though it was not explicitly trained; this was rather a secondary outcome of the functional exercises. Relatively low drop-out rates (21%) suggest that this form of training seems to improve adherence to exercise and may help participants to stay committed to regular, intense activity. By simultaneously triggering adaptations in strength, endurance and whole-body movement skills, this program can be used as a diversified training for people at different training levels.